THE EFFECT OF CURRENT RATIO, TOTAL ASSET TURNOVER, AND EARNINGS PER SHARE ON STOCK PRICES IN BANKING SUB-SECTORS LISTED ON THE INDONESIA STOCK EXCHANGE 2018-2019 - Redy Herinanto Albertus (UPMI Management, 2021)
The purpose of this study was to determine the effect of the variable current ratio, total asset turnover, and earnings per share on stock prices in banking sub-sector companies listed on the Indonesia Stock Exchange in 2018-2019. With a population of 46 companies, a sample of 44 companies was taken obtained through purposive sampling method. By using multiple linear regression analysis, it can be seen that partially current ratio has a positive and significant effect on stock prices, earnings per share has a positive and significant effect on stock prices, and the total asset turnover variable has a positive but not significant effect on stock prices. Simultaneously current ratio, total asset turnover and earnings per share have a significant effect on stock prices.